Assessment of the influence of using green tea waste and fish waste as soil amendments for biosolarization on the growth of lettuce (Lactuca sativa L. var. ramosa Hort.) - Zou, Yunfan; Qiu, Bixia; Lin, Fanqi; Wu, Wanfei; Guo, Runlin; Xing, Jiani; Zhao, Zihui; Shpigelman, Avi; Achmon, Yigal (Frontiers in Sustainable Food Systems, 2023)
Introduction Safe and efficient treatment of organic waste is crucial to developing a sustainable food system around the world. Soil biosolarization (SBS) is a soil treatment technique that can use organic solid wastes to treat the soil in a way that is alternative to the use of chemical fumigants to improve soil fertility in agriculture. Methods In this study, two types of organic food wastes, green tea waste (GTW) and fish waste (FW), were evaluated for the feasibility of being applied as soil amendments within simulations of high-temperature cycle SBS. The evaluation was conducted by execution of three groups of measurements: gas and organic volatile emission profile, residual soil phytotoxicity and weed suppression, and cultivar growth (Lactuca sativa L. var. ramosa Hort.). Results and Discussion Green tea waste contributed to elevated levels of soil respiration and the evolution of signature volatile organic compounds during the simulated SBS. In the soil amended with green tea waste and then undergoing SBS the phyto compatibility was restored after residual phytotoxicity dissipation and a complete weed suppression was achieved. By using an application rate of 2.5% (w/w, mass fraction of green tea waste in total soil-waste mixture) green tea waste cultivar growth comparable to that of the non-treated soil (NTS) group was attained, with a more efficient nitrogen utilization and higher residual soil nitrogen content enabling the improvement of the continuous cropping system. FW at 1% (w/w, mass fraction of FW in total soil-waste mixture) promoted cultivar growth despite the significant reduction of the nitrogen (p value=0.02) and phosphorus (p value=0.03) contents in the cultivar leaves. A significant increase of the sodium content together with an increase of iron and chromium, which exceeded the permissible limit, were observed. These results provide new information about amendment selection for the SBS process.